Analysis of the Characteristics of Stunting Toddler Mothers in the Working Area of the Anak Air Health Center in Padang City - Yaumil Fauziah; Joserizal Serudji; Mayetti Mayetti; Nur Indrawaty Lipoeto; Asrawati Nurdin; Endrinaldi Endrinaldi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The incidence of stunting under five is still a major nutritional problem in Indonesia today. Stunting is a chronic nutritional problem caused by many factors such as age, mother's education and occupation, number of children and birth spacing. The purpose of this study was to analyze the characteristics of mothers who have stunted toddlers in the working area of the Anak Air Health Center in Padang City, West Sumatra Province. This research was conducted in the working area of the Anak Air Health Center in Padang City, West Sumatra Province. The time of the research started from November 2022 to January 2023. This research was an observational study with a descriptive approach. The population for this study was all mothers who had stunting toddlers in the Working Area of the Water Children's Health Center in 2022 as many as 337 people. The research sample was 54 stunting toddlers using a simple random sampling technique. Data collection was carried out using a questionnaire. Data analysis used is descriptive analysis. The results of the study are the characteristics of mothers who have stunted toddlers aged 21-35 years as many as 33 (61.1%), mother's work as housewives as many as 52 (96.3%), high school education as many as 37 (68.5%), the number of children >2 was 31 (57.4%), and the birth spacing was ≥3 years and the first child was 37 (68.5%). It is expected that optimal cross-sectoral cooperation in reducing the prevalence of stunting is according to the government's target, which starts from the first level health service center, namely the community health service center and it is suggested to health workers to provide health education to stunting toddlers about the importance of nutritional needs for toddlers in the process of growth and development. toddler development. Keyword: Characteristics, Education, Number and Spacing of Births, Occupation, Stunting Toddlers